PENGUKURAN KEAKTIFAN DOSEN DALAM PEMBELAJARAN BERBASIS SMARTLECTURER MENGGUNAKAN FUZZY MAMDANI DAN SUGENO - Yasin, Muhammad (POLITEKNIK LP3I JAKARTA, 2019)
The success of learning in a classroom that uses supporting media demands lecturer activity. The level of activity of lecturers in class and using learning media such as Smartlecturer can be measured using a fuzzy logic approach. This study aims to measure the level of active lecturers using the approach, namely: Mamdani and Sugeno method. Stages of lecturer activity measurement by forming a fuzzy set, composition rules as many as 24 rules and the defuzzification process using the centroid method that produces the level of activity of each is low, medium and high. Based on 173 lecturer activity data, the results of the mamdani method low 66%, medium 31%, and high 3%. While the Sugeno method produces a level of activity low 75%, moderate 17%, and high 8%. Therefore, Mamdani method is more suitable for the calculation because the spread of results is relatively evenly distributed at each level. Key words: Lecturer, Fuzzy, Activeness, Mamdani, Sugeno